Analysis of Efficiency for Zakat Management Organization in Indonesia: A Comparison Study of Super Efficiency and Free Disposal Hull - Muhamad Nafik Hadi Ryandono; A Syifaul Qulub; Eko Fajar Cahyono; Tika Widiastuti; Elsi Mersilia Hanesti; Ninda Ardiani; Taqiyah Dinda Insani (Universitas Negeri Jakarta, 2021)
This research aims to analyze the efficiency level of fourteen Zakat Management Organizations (ZMO) in Indonesia. This study uses a quantitative approach with the method of Free Disposal Hull (FDH) and the Super Efficiency (SE) method. Socialization Expense, Operational Expense, and Salary Expense are the input variables, while zakah fund collection and zakah distribution become the output variables. Empirical findings show that ZMO Corp 4 has the highest efficiency level, which analyzed through both methods of FDH or SE. ZMO managed by the government is the most efficient ZMO compared to the others who managed by private group and social organization. Total Potential Importance (TPI) shows that the output variable that requires the most significant adjustment is the zakat distribution, which is 12.66%